1986
DOI: 10.1254/jjp.42.71
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Effects of Dexamethasone and Indomethacin on Bone Wound Healing

Abstract: Abstract-The area of wound holes made in the parietal bone of 4-week-old rats was measured at 1, 2 and 4 weeks after the operation using Alizarin red S staining without the use of histological sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…A proportion of these studies suggest that NSAIDs adversely affect the bone physiology by delaying bone healing and callus formation, impairing bending stiffness and the bones' mechanical properties leading to an increased rate of nonunions [74105]. Some authors have even compared NSAIDs effect on fracture healing with that of other pharmacological agents like steroids [89, 91]. Høgevold et al presented that short-term administration of indomethacin inhibits fracture healing while this was not the case with short-term administration of methylprednisolone [89].…”
Section: Resultsmentioning
confidence: 99%
“…A proportion of these studies suggest that NSAIDs adversely affect the bone physiology by delaying bone healing and callus formation, impairing bending stiffness and the bones' mechanical properties leading to an increased rate of nonunions [74105]. Some authors have even compared NSAIDs effect on fracture healing with that of other pharmacological agents like steroids [89, 91]. Høgevold et al presented that short-term administration of indomethacin inhibits fracture healing while this was not the case with short-term administration of methylprednisolone [89].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that traditional NSAIDS (nonspecific) such as aspirin, indomethacin, and ibuprofen (our definition of NSAID does not include acetaminophen) impede bone healing in various animal models (see Table 1) [20,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. …”
Section: Nsaid Effects On Experimental Models Of Bone Healingmentioning
confidence: 99%
“…These results demonstrate that the non-selective NSAIDs delay fracture healing but do not have any detrimental effects on the ultimate fracture healing outcome in these animal models. Most studies using osteotomy and bone ingrowth models have demonstrated that indomethacin and ibuprofen treatment retards bone healing [29,33,34,35,36,37,38,48,53,54]. In contrast, only a few studies indicate that NSAIDs have little or no effect on fracture healing outcomes [55,56,57,58,59,60].…”
Section: Nsaid Effects On Experimental Models Of Bone Healingmentioning
confidence: 99%
“…Results of these studies are variable. For example, treatment with aspirin, diclofenac, ibuprofen, indomethacin, and tenoxicam, was associated with impaired bone healing in rats and rabbits [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. The main effects observed in those models included inhibition of Haversian (cortical bone) remodeling, alterations in spinal fusions, poor mineralization of bone matrix, decreased osteoid formation and callus bone formation, decreased bone mineral content, reduced mechanical strength of replacement tissue, decreased amounts of cortical bone and inhibition of new bone formation [73,77,[80][81][82][88][89][90][91][92].…”
Section: Effects Of Non-selective Nsaids On Bone Healingmentioning
confidence: 99%